IMPROVING LEARNING OUTCOMES THROUGH PUPPET MEDIA ON ECONOMIC DIVERSI MATERIALS FOR STUDENTS AT SDN SUMOBITO 1 - Nuriddah Nisful Laily; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The existence of learning media is one aspect that supports the quality of learning. Through the use of this learning media, it will be easier for students to understand something that is initially abstract, cannot be observed, heard, or cannot be touched directly. This research is a classroom action research that aims to determine whether the use of visual puppet learning media can improve the learning outcomes of fourth grade students at SDN Sumobito 1 or not. Data collection techniques in this study used the methods of observation, interviews, tests, and documentation. The collected data will be analyzed using qualitative and quantitative approaches. The results of this study indicate an increase in the average learning outcomes and the number of students who complete learning in each cycle. In the pre-cycle the average learning outcome was 54.5 with the percentage of students completing 30%, in the first cycle the average learning outcome was 68 with the percentage of students completing as much as 60%. in cycle II, there was an increase in the average learning outcome to 78.5, with the percentage of students completing 85%. This shows that the use of visual puppet media can improve the learning outcomes of fourth grade students at SDN Sumobito 1.